2018
DOI: 10.3892/etm.2018.5717
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of miconazole on rat myelin sheaths following premature infant cerebral white matter injury

Abstract: The aim of the present study was to investigate the protective effects of miconazole on myelin sheaths following cerebral white matter damage (WMD) in premature infant rats. Sprague Dawley rats (3-days-old) were randomly divided into four groups (n=30 each) as follows: Sham surgery group, WMD model group, 10 mg/kg/day treatment group and 40 mg/kg/day treatment group. A cerebral white matter lesion model was created by ligating the right common carotid artery for 80 min. Treatment groups were administered with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…Previous research has shown that the neonatal rat WMI model display decreased motor function and impaired spatial working memory [11,40]. In the present study, we provided in vivo evidence that ZJU-37 combined with hOPCs improved cognitive and motor function compared to ZJU-37 or OPCs alone in WMI rats, as shown by behavioural tests.…”
Section: Discussionsupporting
confidence: 67%
“…Previous research has shown that the neonatal rat WMI model display decreased motor function and impaired spatial working memory [11,40]. In the present study, we provided in vivo evidence that ZJU-37 combined with hOPCs improved cognitive and motor function compared to ZJU-37 or OPCs alone in WMI rats, as shown by behavioural tests.…”
Section: Discussionsupporting
confidence: 67%
“…Miconazole and Clobetasol act as two potent inducers of oligodendrocyte differentiation, as they trigger fast maturation of MBP + cells in both physiological and pathological conditions (Najm et al , ; Su et al , ). Given our observations, we asked whether a similar treatment could be of use in the BBSOA mouse model of optic neuropathy.…”
Section: Resultsmentioning
confidence: 99%
“…This is in accordance with ON hypomyelination at P8, although with different severities between HET and KO , and in HET mutants at P28. Strikingly, postnatal treatment with Miconazole, a potent inducer of oligodendrocyte differentiation in several brain regions (Najm et al , ; Su et al , ), efficiently rescues the myelination grade of Nr2f1 mutants via ERK signaling activation, showing that this chemical drug can counteract hypomyelination in the context of the BBSOA mouse model. This is a first step not only in understanding the pathophysiological features of a complex syndrome, but also in proposing possible therapeutic approaches.…”
Section: Discussionmentioning
confidence: 99%
“…White matter damage of premature infants is one of the most common causes of cerebral palsy, audiovisual obstacles, intelligence development retardation, epilepsy, learning difficulty and other brain damage syndromes, which seriously influence their quality of life (10). Prior studies have shown that there is a close relation between the occurrence of newborn brain damage and the fetal age (especially related to the low cerebrovascular developmental maturity of premature infants) (11).…”
Section: Discussionmentioning
confidence: 99%